Optimal selection of machining datum and machining tolerance allocation through tolerance charting. (9th July 2012) - Thilak, M.; Sivakumar, K.; Jayaprakash, G.
The main purpose of tolerance charting is to determine the optimal allocation of working dimensions and working tolerances such that the blueprint dimensions and tolerances can be achieved to accomplish the cost objectives. The selection of machining datum and allocation of tolerances are critical in any machining process planning as they directly affect any setup methods/machine tools selection and machining time. In order to reduce the machining time and cost, an optimum process plan should be designed. Due to the existence of intermediate machining operation, a large number of intermediate part features may be used as the datum for the machining of others. This paper mainly focuses on the selection of optimum machining datums and machining tolerances simultaneously in process planning. In this work, an optimisation model is formulated for selecting machining datum and tolerances and implemented with an evolutionary algorithm namely differential evolution (DE).